Opportunities and challenges of food policy councils in pursuit of food system sustainability and food democracy–a comparative case study from the Upper-Rhine region - Michel, Sophie; Wiek, Arnim; Bloemertz, Lena; Bornemann, Basil; Granchamp, Laurence; Villet, Cyril; Gascón, Lucía; Sipple, David; Blanke, Nadine; Lindenmeier, Jörg; Gay-Para, Magali (Frontiers in Sustainable Food Systems, 2022)
Conventional food systems continue to jeopardize the health and well-being of people and the environment, with a number of related Sustainable Development Goals (SDGs) still far from being reached. Food Policy Councils (FPCs)—since several decades in North America, and more recently in Europe—have begun to facilitate sustainable food system governance activities among various stakeholders as an explicit alternative to the shaping of food systems by multinational food corporations and their governmental allies. In contrast to the former, FPCs pursue the goals of food system sustainability through broad democratic processes. Yet, at least in Europe, the agenda of FPCs is more an open promise than a firm reality (yet); and thus, it is widely unknown to what extent FPCs actually contribute to food system sustainability and do so with democratic processes. At this early stage, we offer a comparative case study across four FPCs from the Upper-Rhine Region (Freiburg, Basel, Mulhouse, Strasbourg)—all formed and founded within the past 5 years—to explore how successful different types of FPCs are in terms of contributing to food system sustainability and adhering to democratic and good governance principles. Our findings indicate mixed results, with the FPCs mostly preparing the ground for more significant efforts at later stages and struggling with a number of challenges in adhering to principles of democracy and good governance. Our study contributes to the theory of sustainable food systems and food democracy with the focus on the role of FPCs, and offers procedural insights on how to evaluate them regarding sustainable outcomes and democratic processes. The study also offers practical insights relevant to these four and other FPCs in Europe, supporting their efforts to achieve food system sustainability with democratic processes.